MECHANICAL CHARACTERIZATION OF WASTE POLYETHYLENE SYNTHESIZED VIA Ni NANO COMPOSITE - RIFKATU, K.D.,; BORYO, D.E. A.,; CHINDO, I.Y.,; SHIBDAWA, M.A. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
The mechanical properties of polymer are one of the important factors to be considered in determining the capability of using the material for electrical, construction and biomedical applications. In this study we assessed the effect of Nickel (Ni)nanoparticles on mechanical properties of waste polyethylene. Waste polyethylene/green synthesized Ni nanocomposite was prepared using solution method of polymerization. The nanoparticle of Ni was synthesis from garlic bark aqueous solutions. The mechanical properties were investigated using a shore ‘A’ durometer and Instron universal testing machine. The percentage elongation at break increases from 78.0 % to 86 %, the hardness of nanocomposite increases from 94.2 N/mm² to 94.40 N/mm², as well as increase in flexural strength from 13.62 Mpa to 14.35 Mpa. Themodulus of elasticity of the waste polyethelene/green Ni nanocomposite decreases drastically from 1.76 Mpa to 1.08 Mpa, and tensile strength of the nanocomposite decreases from1.13 Mpa to 0.6 Mpa. These mechanical properties are important to the field of nanotechnology to certify and facilitate the fabrication of high performing polymer for complex application in the field of electrical and biomedical nanotechnology.